1982
DOI: 10.1007/bf00254838
|View full text |Cite
|
Sign up to set email alerts
|

The effect of insulin antibodies on insulin dose and diabetic control

Abstract: Summary.In a single blind randomised cross-over study, 40 patients were changed from ordinary bovine to highly purified porcine insulins for a period of 6 months. Half were later rechallenged with bovine insulin. Sequential determinations of IgG insulin binding capacity for bovine insulin were correlated with insulin dose and diabetic control. After changing to highly purified insulins the following correlations were observed between percentage change in insulin dose and change in insulin binding capacity: at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 16 publications
1
27
1
Order By: Relevance
“…Previous studies have shown that changing from conventional bovine to highly purified porcine insulin (i. e. a change in both species and purity) reduces levels of insulin antibody and antibodies reactive with other pancreatic peptides and hormones [2,3,7,12]. However, we [7] found that a reduction in proinsulin contamination of bovine insulin to 20-40 ppm did not lower antibody levels in patients previously "immunised" with a conventional bovine preparation.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Previous studies have shown that changing from conventional bovine to highly purified porcine insulin (i. e. a change in both species and purity) reduces levels of insulin antibody and antibodies reactive with other pancreatic peptides and hormones [2,3,7,12]. However, we [7] found that a reduction in proinsulin contamination of bovine insulin to 20-40 ppm did not lower antibody levels in patients previously "immunised" with a conventional bovine preparation.…”
Section: Discussioncontrasting
confidence: 55%
“…Starter and Switch groups were subsequently treated with semi-synthetic human isophane insulin for 6 months during which insulin antibody levels fell significantly from a geometric mean of 8.5 to 4.4 ~tg/1 (p< 0.001). We conclude that bovine insulin purified to less than 1 ppm proinsulin is significantly less immunogenic than its conventional proinsulin contaminated counterpart but even at this level of purity is still more immunogenic than human insulin of equivalent purity.Key words: Immunogenicity, Bovine insulin, Lipoatrophy, Insulin antibodies, Human insulin Previous studies [1][2][3] have shown that bovine insulin purified by sequential recrystallisation to > 1000ppm proinsulin (conventional bovine insulin) is much more immunogenic that its highly purified ( < 1 ppm proinsulin) porcine counterpart. Not only are levels of insulin antibody higher but antibodies to C-peptide and other islet proteins are often present after using the conventional preparation [3][4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The production of insulin antibody is not only of academic interest for it does have a role in insulin allergy, injection site lipoatrophy [17] and some types of insulin resistance as well as having more subtle effects on the dose requirement, and on the pharmacokinetics of injected insulin [18][19][20][21]. Insulin-antibody complexes may have a deleterious effect in patients with vascular disease but there are insufficient data to be sure.…”
mentioning
confidence: 99%
“…Alternatively, it is feasible that the AIA are having a partial neutralising effect on insulin activity, which would therefore require higher doses of insulin to maintain glycaemic control. In human diabetic patients, it has been shown that high levels of circulating AIA can affect the dose of insulin required to maintain glycaemic control and that by changing to a less immunogenic insulin there is a reduction in AIA and the dose of insulin required by the patient (Walford et al, 1982).…”
Section: Discussionmentioning
confidence: 99%